A Two-Step Ensemble-based Genetic Algorithm for Land Cover Classification - Cao, Yang; Feng, Wei; Quan, Yinghui; Bao, Wenxing; Dauphin, Gabriel; Song, Yijia; Ren, Aifeng; Xing, Mengdao (IEEE journal of selected topics in applied earth observations and remote sensing, 2023)
Accurate land use and land cover (LULC) maps are effective tools to help achieve sound urban planning and precision agriculture. As an intelligent optimization technology, genetic algorithm (GA) has been successfully applied to various image classification tasks in recent years. However, simple GA faces challenges such as complex calculation, poor noise immunity, and slow convergence. This research proposes a two-step ensemble protocol for LULC classification using a grayscale-spatial-based genetic algorithm model. The first ensemble framework uses FCM to classify pixels into those that are difficult to cluster and those that are easy to cluster, which aids in reducing the search space for evolutionary computation. The second ensemble framework uses neighborhood windows as heuristic information to adaptively modify the objective function and mutation probability of the genetic algorithm, which brings valuable benefits to the discrimination and decision of GA. In this study, three research areas in Dangyang, China, are utilized to validate the effectiveness of the proposed method. The experiments show that the proposed method can effectively maintain the image details, restrain noise, and achieve rapid algorithm convergence. Compared with the reference methods, the best overall accuracy obtained by the proposed algorithm is 88.72%.